2016
DOI: 10.9741/23736658.1044
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a culturally tailored web-based physical activity promotion program on Asian American midlife women’s depressive symptoms

Abstract: The benefits of physical activities on depressive symptoms have increasingly been reported in the literature, but the effect through which a Web-based physical activity promotion program alleviates depressive symptoms is not clearly known, especially among ethnic minority midlife women. The purpose of this pilot randomized control study is to examine the preliminary efficacy of the Web-based physical activity promotion program in enhancing the depressive symptoms of Asian American midlife women through increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 41 publications
0
30
0
Order By: Relevance
“… 61 In two studies, the samples were a mixture of participants with and without depression and/or anxiety symptoms, but the data were merged. 62 , 63 The authors were contacted through e-mail and ResearchGate but they did not respond, and these studies were excluded.…”
Section: Resultsmentioning
confidence: 99%
“… 61 In two studies, the samples were a mixture of participants with and without depression and/or anxiety symptoms, but the data were merged. 62 , 63 The authors were contacted through e-mail and ResearchGate but they did not respond, and these studies were excluded.…”
Section: Resultsmentioning
confidence: 99%
“…Comparative intervention included websites for health promotion, 22,25,26,29 attention control, 24 and usual care. 21,30 One study compared the effects of health coaching provided by different types of coaches: professional, peer participants, and mentor.…”
Section: Resultsmentioning
confidence: 99%
“…First, some studies did not report all data at different timepoints of measurement and data from the participants who withdrew from the study. [24][25][26]29 Second, some studies were at risk of detection bias because the outcome assessors were not blinded to the group allocation or because of lack of the information reported. 24,31 Third, some studies were at risk of selection bias because the participants were not randomized to the groups 22 and because of insufficient reports on allocation concealment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More detailed information on the parent study and the interventions could be found elsewhere (“A Pilot Physical Activity Intervention Study on Depressive Symptoms of Midlife Korean Americans” [in preparation]). 28,29…”
Section: The Parent Study: Basis For Discussionmentioning
confidence: 99%